The spatial distribution of cystic echinococcosis in Italian ruminant farms from routine surveillance data - Entezami, Mahbod; Nocerino, Martina; Widdicombe, Jo; Bosco, Antonio; Cringoli, Giuseppe; Casulli, Adriano; Iacono, Giovanni Lo; Rinaldi, Laura; Prada, Joaquin M. (Frontiers in Tropical Diseases, 2022)
Introduction Cystic echinococcosis (CE) is a zoonotic parasite caused by the cestode Echinococcus granulosus sensu lato (s.l.) which predominantly affects livestock. The disease is endemic in central-southern and insular Italy, with CE particularly infecting sheep, goats, cattle, and water buffalo. The spatial distribution of CE in endemic regions is not widely understood, with surveillance efforts varying across the region. Methods In this study, we investigated the spatial distribution of CE in livestock using samples from farms across different livestock species using a Stochastic Partial Differential Equations (SPDE) model. Samples were collected during a survey conducted in the area of central-southern and insular Italy between the years 2019 – 2021. Results A total of 3141 animal samples (126 goats, 601 sheep and 2414 cattle and water buffalo) were inspected for Echinococcus s.l. cysts through routine surveillance in abattoirs by postmortem visual examination, palpation and incision of target organs. The geographic location of the farm of origin (a total of 2,878) for each sample was recorded. CE prevalence of 46.0% (1,323/2,878) was estimated at the farm level with 78.3% (462/590) of farms with sheep, 28.6% (36/126) of farms with goats, 36.5% (747/2,049) of farms with cattle, and 23.5% (102/434) of farms with water buffalo infected. Discussion The spatial model evaluated the probability of infection in farms across the sampled regions, with the distribution of CE showing high clustering of infected cattle farms in Sardinia and Sicily regions, and sheep farms in Salerno province (Campania region). The output of this study can be used to identify CE hot-spots and to improve surveillance and control programs in endemic areas of Italy.